2017
DOI: 10.1002/jat.3506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four different fuller's earth formulations in skin decontamination

Abstract: Industrial accidents, wars and terrorist threats are potential sources of skin contamination by highly toxic chemical warfare agents and manufacturing compounds. We have compared the time-dependent adsorption capacity and decontamination efficiency of fuller's earth (FE) for four different formulations for the molecular tracer, 4-cyanophenol (4-CP), in vitro and ex vivo using water decontamination as standard. The adsorption capacity of FE was assessed in vitro for 4-CP aqueous solutions whereas decontaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This finding is in agreement with that of Babavatan and his coworkers where they found that immobilized lipase was protected from denaturing by the support [39]. In addition to this, FE is also known to be a fireretardant material, and is able to displace heat, which may also be a reason for its stability [18]. Therefore, the improved thermostability of immobilized YT PTE is an important observation and is likely to have an impact on practical applications of this enzyme.…”
Section: Characterization Of the Immobilized Yt Pte 221 Effect Of Temperature On Immobilized Yt Pte Activity And Stabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in agreement with that of Babavatan and his coworkers where they found that immobilized lipase was protected from denaturing by the support [39]. In addition to this, FE is also known to be a fireretardant material, and is able to displace heat, which may also be a reason for its stability [18]. Therefore, the improved thermostability of immobilized YT PTE is an important observation and is likely to have an impact on practical applications of this enzyme.…”
Section: Characterization Of the Immobilized Yt Pte 221 Effect Of Temperature On Immobilized Yt Pte Activity And Stabilitysupporting
confidence: 90%
“…The major components found in FE include montmorillonite (MMT), various mixtures of kaolinite and attapulgite/bentonite. Moreover, FE is an already known compound and is in common use as a high adsorption material, which has been utilized as an adjunct in the treatment of poisoning, as a decontamination agent in chemical accidents, in various cleaning processes as an adsorbent, as a component ingredient in cosmetic products and has been used as support for immobilized enzymes [18,19]. It has been stated in the literature that most of the enzymes that can be immobilized onto mineral or natural supports such as bentonite, MMT, halloysite and kaolinite can be attached without restriction [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…82 In specific, known exposures, other decontamination agents may be more effective: a study of the molecular tracer 4-cyanophenol found that decontamination efficiency from porcine skin was 54% with water, up to 70% with dry fuller's earth, and around 90% with a suspension of fuller's earth. 83 In terms of wet versus dry decontamination, another study of absorbent materials in an ex vivo model indicated that dry decontamination was superior to wet methods for removing liquid contaminants but was not effective against particulate matter. 84 The consensus among investigators, however, is that time is the single most important factor in successful decontamination.…”
Section: Decontaminationmentioning
confidence: 99%
“…He found it better than most of other powders and pastes tested. This observation is particularly intriguing as Fuller's Earth is currently being investigated for its effectiveness in sulfur mustard decontamination, and is known as an effective decontaminant for lewisite exposure (Marrs, 2007;Roul et al, 2017;Taysse, Daulon, Delamanche, Bellier, & Breton, 2007).…”
Section: Work On Rapid Penetration Of Dichlorethyl Sulfide and Its mentioning
confidence: 99%